2016
DOI: 10.1177/0963721416657050
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of How Dogs Became Our Social Allies

Abstract: Dogs were domesticated from wolves about 15000 years ago and an important selection pressure (intentional or unintentional) has been their ability to communicate and cooperate with us. They show extensive human-directed sociability, which varies within as well as between breeds and which is not shared by ancestral wolves. Hence, dogs are potentially ideal models for studying the genetics of social behaviour. Here we review some recent research carried out by others and us on this subject. We present results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Oxytocin receptor genes have also been investigated in other domestic species; for example, in cats researchers found that the G738A OXTR SNP was associated with the personality trait “Roughness” (irritable, dominant, forceful, and moody behavior), as reported by owner questionnaire (Arahori et al, 2016 ). However, oxytocin has received the most extensive interest in how it may modulate dogs' behavior toward humans (Buttner, 2016 ; Jensen et al, 2016 ; Thielke and Udell, 2017 ). For example, intranasal administration of oxytocin was found to enhance motivation to approach and affiliate with owners (Romero et al, 2014 ), and increase looking back at human partners in a situation involving threatening behavior signals by a human (Hernádi et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oxytocin receptor genes have also been investigated in other domestic species; for example, in cats researchers found that the G738A OXTR SNP was associated with the personality trait “Roughness” (irritable, dominant, forceful, and moody behavior), as reported by owner questionnaire (Arahori et al, 2016 ). However, oxytocin has received the most extensive interest in how it may modulate dogs' behavior toward humans (Buttner, 2016 ; Jensen et al, 2016 ; Thielke and Udell, 2017 ). For example, intranasal administration of oxytocin was found to enhance motivation to approach and affiliate with owners (Romero et al, 2014 ), and increase looking back at human partners in a situation involving threatening behavior signals by a human (Hernádi et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…During the course of domestication, dogs seem to have evolved impressive interspecific cooperation skills with humans ( Jensen et al, 2016 ; Miklósi & Topál, 2013 ). For example, comparative studies have shown that dogs have a higher sociability in general than wolves ( Bentosela et al, 2016 ) and, specifically, that dogs seek more human contact when faced with a problem than wolves do ( Heberlein et al, 2016 ; Miklósi et al, 2003 ; Udell, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggest that domestic dogs represent the ideal subjects for studying the genetics of social behavior (Jensen et al, ) and the evolution of a human‐analog social competence (Miklósi & Topál, ). In line with this idea, recent genetic studies have identified candidate genomic regions associated with human‐directed social behaviors in dogs (Kis et al, ; Persson, Wright, Roth, Batakis, & Jensen, ) and an experimental investigation of behavioral variations within a certain breed (Bull Terrier) revealed behavioral and endocrine phenotypes similar to the clinical presentation of human autism (Tsilioni et al, ).…”
Section: Translational Approaches To Understand Autism: Potentials and Limitationsmentioning
confidence: 99%